Hedge Accounting and Risk Management: An Advanced Prospective Model for Testing Hedge Effectiveness. (February 2015) - Di Clemente, Annalisa
<x xml:space="preserve">Abstract</x> In this work we propose a new prospective model for testing the economic hedge effectiveness. Our model is derived from the initial approach based on the measure of the relative risk reduction (RRR) where the risk is expressed by the standard deviation and a Normal world is assumed. Differently, our model estimates the RRR produced by the hedging strategy in terms of the new risk measures of the value at risk (VaR) and the expected shortfall (ES). Moreover, it fails the traditional hypothesis of a normal distribution for the risk factors generating their return scenarios by Monte Carlo simulation. Because the main hedging issue especially for financial institutions is the portfolio hedging, our model has been implemented to a market risk hedging strategy, the cross hedging, realized by combining a stock index future (short position) with a stock portfolio (long position). We underline that, while our results present a strong significance from an economic viewpoint, they may be utilized only in an experimental way for hedge accounting purposes.